Akselerasi Inklusi Keuangan Melalui Inovasi Lembaga Keuangan Syariah di Indonesia - Syarifah Ajijah; Siti Aisyah; Mutia Rahmania Fitriyani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Financial inclusion is an important pillar in equitable economic development, especially in Indonesia with a majority Muslim population. However, the contribution of Islamic financial institutions (LKS) to national financial inclusion is still low due to limited innovation, access, and public literacy about Islamic finance. This study aims to analyze the role of LKS innovation in accelerating financial inclusion in Indonesia. The research method uses a descriptive qualitative approach with literature studies and secondary data analysis from various related reports and publications. The results show that service digitalization, product diversification, and strengthening the halal ecosystem are the main strategies of LKS innovation. Digital innovations such as sharia mobile banking, fintech, as well as microfinance services and the halal sector have proven effective in expanding access to Islamic finance, especially for MSMEs and communities in remote areas. Synergy between the government, regulators, and industry players is needed to create an inclusive and sustainable Islamic financial ecosystem. The implications of this study emphasize the importance of continuous innovation and Islamic financial literacy education to increase the role of LKS in supporting national economic growth based on Islamic values.